The Effect Of Administrative Drug Due To Oxidative Stress On HIV Patients : A Literature Reviev - Figa Danang Hidayatulloh (Center for Biomechanics, Biomaterials, Biomechantronics and Biosignal Processing (CBOIM3S), 2022)
ABSTRACTHIV-related neurocognitive problems have been associated with elevated levels of cerebrospinal fluid (CSF) as indications of oxidative stress, nerve damage, and inflammation as well as lower levels of neurotransmitters (HAND). HIV-related neurocognitive problems have been associated with elevated levels of cerebrospinal fluid (CSF) as indications of oxidative stress, nerve damage, and inflammation as well as lower levels of neurotransmitters (HAND). This study aims to collect and analyze articles related to drug administration in HIV patients. The design used is a literature review. Search articles were collected using the PubMed database by entering the keywords HIV, Oxidative Stress, and Effect. Since it is known that there is a stress process oxidative stress in HIV patients a type of antioxidant developed for protection against the occurrence of HIV a mixture of various antioxidants that do not dangerous like vitamins and their derivatives able to suppress the symptoms of HIVKeywords : HIV, Oxidative Stress, Effect On HIV